Pattern of T-cell non-Hodgkin's lymphoma in a tertiary care center in North East India - Debanwita Mahanta; Jagannath Dev Sharma; Anupam Sarma; Lopamudra Kakoti; Amal Chandra Kataki; Shiraj Ahmed (Indian Journal of Medical and Paediatric Oncology)
Context: The non-Hodgkin's lymphomas (NHLs) are lymphoid neoplasms that arise primarily in the lymph nodes. They are classified into B-cell, T-cell, and natural killer cell types and are subtyped on the basis of morphologic and immunohistochemical studies. T-cell neoplasms are clonal tumors of mature and immature T-cells at various stages of differentiation. T-cell lymphoma is common in Asia compared to Europe and America. The pattern and prevalence of T-cell lymphoma in India are, however, different from that of other Asian countries. Aims: The main aim of this study is to analyze the prevalence and pattern of T-cell NHL in North East India, as less number of studies have been carried out in this part of the country. Settings and Design: A 5-year retrospective study (2012–2016) was carried out in our institute, which is a regional cancer center located in North East India. Materials and Methods: Five-year records of previously diagnosed cases were obtained, and then the hematoxylin- and eosin-stained sections and the immunohistochemistry slides were reviewed and studied. Results: A total number of 294 cases of NHL were reviewed in the study period. Seventy-one cases were found to be of T-cell NHL type which comprised 24% of the total NHL. Peripheral T-cell lymphoma not-otherwise specified (PTCL-NOS) (62%) was the most common followed by anaplastic large cell lymphoma (27%). T-lymphoblastic lymphoma (7%) was common in children and young adults. Conclusion: PTCL-(NOS) was found to be the most common T-cell lymphoma. Treatment of most of the cases was by chemotherapy using the cyclophosphamide, doxorubicin, vincristine, and prednisone regimen.